Blended Learning Berbasis Instagram Solusi Pembelajaran Kreatif Di Tengah Pandemi Covid-19 - Sulistyorini, Dwi Ermavianti Wahyu (Jurnal Riset Daerah, 2021)
The objectives of this study include, 1) Optimizing the learning of Instagram-based blended learning models in pkwu subject classes, 2) Providing positive impact and new experiences in learning for students to become an entrepreneurship in the classroom. At the time of the pandemic suddenly teachers and students are faced with distance learning, without exception productive subjects that are practical learning so that teachers must think creatively so that students can still carry out practices at home. The difficulties experienced during this online learning activity include; 1) learning practices of Creative Products and Entrepreneurship are constrained online; 2) students are often constrained by quotas and signals; 3) not all social media can contain interactive videos / images that can record activities performed by students; 4) the collection of student assignments is not on time. The learning solution conducted by teachers is to implement instagram-based blended learning model in the students of grade XII TK 2 as many as 27 people. A blended learning model is learning that combines a variety of web-based technologies to achieve learning goals, or a combination of face-to-face with online classes. In its implementation, teachers use social media as a learning support, namely Instagram. With research procedures using descriptive research methods with qualitative folding and written empirically based on the teacher's experience during teaching. The results achieved from this activity have a positive impact on students, namely to be more responsible and disciplined (entrepreneurship) in following online and offline learning. Practical learning can be dissolution with practice at home and presented via Instagram live streaming, while the effectiveness that emerges is; 1) as many as 70% of students are happy because it can be a home practice solution supervised by teachers online; 2) the emergence of a sense of responsibility of students to the practice schedule that has been prepared without being ordered or forced; 3) the emergence of a sense of self-reliantness for work or practical actions performed online; 4) collection of timely student assignments offline